ANALISIS KOREKSI FISKAL UNTUK MENGHITUNG PPH BADAN PADA PT. EMPAT TUJUH ABADI JAYA - Tulandi, Mesias Ridel; Sabijono, Harijanto; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
PT. Empat Tujuh Abadi Jaya is a company that is a taxpayer in the form of a body that has responsibility to calculate, deposit and report the tax payable that must be paid to the state based on self-assessment system that gives full trust to the taxpayer in reporting corporate tax. But there is a problem that will be faced in the payment of taxes. This is due to the fact that the financial statements in particular the income statements are different from the commercial profit referring to the Financial Accounting Standards while the fiscal profit refers to the applicable Taxation Law. This difference is simply in the presence of income and expenses recognized as income or expenses by the company but is not recognized by the tax and in the filling as the company does not pay attention to the fiscal correction in tax reporting. For that company must pay attention to fiscal correction / fiscal reconciliation so that the amount of corporate tax payable can be equal to tax. The purpose of this study is to determine the fiscal profit derived from the results of fiscal correction in commercial financial statements to determine the tax payable body. In this study, earnings obtained after the fiscal correction in the financial statements of Rp201,112,732.00 and profit before the fiscal correction of Rp181.510.720,00 for the calculation of corporate taxes using tarif 17 paragraph 2a with tarif 25% Act No. 36 of 2008 Tax The income of the company must pay the tax before it is made Rp45.377.680,00 for the corporate tax rate less attention to the Article 31 E fare with 50% discount from the normal tarif of 25% gross turnover Rp4.8.000.000.000,00 or below and up to Rp50. 000.000.000,00 billion got a discount. Gross circulation of PT. Empat Tujuh Abadi Jaya shall not exceed 4.8M amounting to Rp4,669,400,000.00, so the Company is permitted to use the rate of article 31 E. Keywords: Tax due, Income Statement, Fiscal Correction.